2021
DOI: 10.3390/biomedicines9020179
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of New Cancer Stem Cell-Related Genes and Their Regulatory microRNAs in Colorectal Cancerogenesis

Abstract: Significant progress has been made in the last decade in our understanding of the pathogenetic mechanisms of colorectal cancer (CRC). Cancer stem cells (CSC) have gained much attention and are now believed to play a crucial role in the pathogenesis of various cancers, including CRC. In the current study, we validated gene expression of four genes related to CSC, L1TD1, SLITRK6, ST6GALNAC1 and TCEA3, identified in a previous bioinformatics analysis. Using bioinformatics, potential miRNA-target gene correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…MiR-940 interdicts proliferation and migration of cancer cells and miR-1225-3p implicates malignancy. These two miRNAs interact with CDCP1 [ 48 , 49 ]. Moreover, miR-423-3p is an oncomir that boosts cancer cell proliferation through the promotion of the G1/S transition phase of the cell cycle [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-940 interdicts proliferation and migration of cancer cells and miR-1225-3p implicates malignancy. These two miRNAs interact with CDCP1 [ 48 , 49 ]. Moreover, miR-423-3p is an oncomir that boosts cancer cell proliferation through the promotion of the G1/S transition phase of the cell cycle [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified several pathways that can be associated with CSC alone or both CSC and extracellular matrix (ECM). Some of them were identified by our group in previous studies, associated with the ECM and CSC, and were already validated in CRC development [ 4 , 54 ]. The identified pathways in current study were the ECM-receptor interaction pathway [ 55 ], PPAR signaling pathway [ 56 ], and the PI3K-Akt signaling pathway [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that genes related to CSC-like cells might be also involved in development and progression of colorectal cancer (CRC) [ 4 , 5 ]. CRC is one of the most common causes of morbidity due to cancer worldwide [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLITRK6 , one of six members of the SlitRK family of transmembrane proteins, has been found to be closely involved in cell adhesion, cell differentiation, stem cell characterization, cancer cell migration, and invasion [ 41 , 42 ]. Studies have shown that SLITRK6 is moderately negatively correlated with tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%